Faktor-Faktor Yang Mempengaruhi Audit Delay (Studi Kasus Pada Perusahaan LQ-45 Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2020) - Supriono Supriono; Dwi Fitriani (Politeknik Sawunggalih Aji, 2022)
At this time the development of business in Indonesia is very rapid, this is indicated by the number of companies that have gone public and are listed on the Indonesia Stock Exchange (IDX). This development was also marked by the increase in the number of companies listed on the Indonesia Stock Exchange for five consecutive years, namely in 2016 there were 539 listed companies, in 2017 there were 574 companies listed, and in 2018 there were 629, in 2019 there were 668 companies. , and in 2020 there were 709 listed companies. Financial statements are something that is very important for the sustainability of a company, especially companies that have gone public. Companies that have gone public must be able to present financial statements that are able to provide good and relevant information for investors so that they can be used as a basis for making decisions by investors. The type of data used in this research is quantitative data. The data taken is from the annual financial statements of LQ-45 companies listed on the IDX for the 2016-2020 period. The data analysis technique used in this study uses descriptive statistics, classical assumption test and multiple regression analysis. The population in this study are LQ-45 companies listed on the Indonesia Stock Exchange for the 2016-2020 period, which are 34 companies. The technique used in sampling is purposive sampling The results of this study are, solvency has a negative and significant effect on audit delay, firm size has a negative and insignificant effect on audit delay, KAP reputation has a positive and insignificant effect on audit delay, type of industry has a negative and significant effect on audit delay, company age has a negative effect. and not significant to audit delay. Solvency, company size, KAP reputation, type of industry and age of the company together have a significant effect on audit delay.